Sufi and Taoist Heritage and Glocalism or Two Types of Civilizations and Two Kinds of Dialogue - Eshots, Yanis (Afkar: Jurnal Akidah dan Pemikiran Islam, 2006)
On the basis of Izutsu's study "Sufism and Taoism", I attempt to demonstrate the similarity of the basic intuitions of Sufism and Taoism, namely, those of the unity-in-manyness, the self-evolvement of existence and the perpetual inner transformation of Man. I argue that only on the philosophical level mutual understanding between civilizations can result in lasting metaphysical dialogue. Such dialogue, if it is led methodically, can give rise to perennial philosophy in the true sense of the term.If it is possible to achieve in principle a harmony between the contradictory tendencies of globalization and localism, such harmony can only be established on the level of metaphysical dialogue.